Demoralization: Where it stands-and where we can take it: A bibliometric analysis - Zheng, Qingyong; Xiong, Lu; Li, Huijun; Liu, Ming; Xu, Jianguo; Luo, Xiaofeng (Frontiers in Psychology, 2022)
Objectives: The purpose is to analyze existing studies related to the field of demoralization through bibliometrics. Methodology: Relevant literature on demoralization was searched from PubMed, Web of Science, the Cochrane Library, and CINAHL Complete. Bibliometric analysis was performed using GraphPad Prisma 8.2.1, VOSviewer 1.6.18 and R software. Research publication trends, author-country collaboration, research hotspots and future trends were explored by generating network relationship maps. Results: A total of 1035 publications related to the field of demoralization were identified. The earliest relevant studies have been published since 1974, and the studies have grown faster since 2000. Psyche-oncology and Psychother Psychosom had the highest number of publications (n=25). The United States, Italy and Australia have made outstanding contributions to the field and there was an active collaboration among leading scholars. Major research hotspots include the multiple ways of assessing demoralization, the specificity of various demographics and psychological disorders in different disease contexts, and the association and distinction of diverse clinical psychological abnormalities. the impact of COVID-19 on demoralization and subsequent interventions and psychological care may become a future research direction. Conclusion: There has been a significant increase in research in the field of demoralization after 2000. The United States provided the most publications. There is overall active collaboration between authors, countries, and institutions. In future research, more attention will be paid to the effects of COVID-19 on demoralization and intervention care for this psychology.